Microbial synergism between essential oils and synthetic preservatives used in the food industry (Research, Society and Development, 2022)
The use of food additives is necessary for the distribution of food, but due to the concern of consumers with food, the food industry increasingly seeks to reduce the use of synthetic additives, without reducing the quality of its products. Therefore, this work aimed to evaluate the antimicrobial effect of essential oils by the disk-diffusion method, the minimum inhibitory concentration (MIC) in microplates and their possible synergism with synthetic antimicrobials normally used by the industry by the "checkerboard" method. Among the evaluated oils (Rosemary, Basil, Tangerine, Peppermint and Copaíba), Basil showed the highest antimicrobial activities in the disk diffusion test and Copaíba, the lowest. In the MIC analysis, it was observed that Rosemary and Copaíba were more effective against L. monocytogenes and S. aureus (0.31 mg.mL-1); Basil against S. Typhimurium and L. monocytogenes (0.62 mg.mL-1); Tangerine against L. monocytogenes (0.31 mg.mL-1) and Peppermint against B. cereus (0.62 mg.mL-1). Synthetic antimicrobials were effective against all bacteria and their concentration varied between 15 and 1.5 mg.mL-1. When analyzing the synergism test, it was verified that the oil that presented the most predominant synergistic associations was Basil, while the other oils had more indifferent or additive associations. Therefore, the present research concludes that there is in vitro synergism between synthetic antimicrobials and essential oils, creating a possibility for the food industry to reduce the use of synthetic additives by applying these associations in their products.